Against The Romance Of Community - Joseph, Miranda (Book collections on Project MUSE., 2002)
Miranda Joseph explores sites where the ideal of community relentlessly recurs, from debates over art and culture in the popular media, to the discourses and practices of nonprofit and nongovernmental organizations. She shows how community legitimates the social hierarchies of gender, race, nation, and sexuality that capitalism implicitly requires. Exposing the complicity of social practices, identities, and communities with capitalism, this truly constructive critique opens the possibility of genuine alliances across such differences.